Genome diversity in the Neolithic Globular Amphorae culture and the spread of Indo-European languages. Issue 1867 (22nd November 2017) - Tassi, Francesca; Vai, Stefania; Ghirotto, Silvia; Lari, Martina; Modi, Alessandra; Pilli, Elena; Brunelli, Andrea; Susca, Roberta Rosa; Budnik, Alicja; Labuda, Damian; Alberti, Federica; Lalueza-Fox, Carles; et al.
Abstract : It is unclear whether Indo-European languages in Europe spread from the Pontic steppes in the late Neolithic, or from Anatolia in the Early Neolithic. Under the former hypothesis, people of the Globular Amphorae culture (GAC) would be descended from Eastern ancestors, likely representing the Yamnaya culture. However, nuclear (six individuals typed for 597 573 SNPs) and mitochondrial (11 complete sequences) DNA from the GAC appear closer to those of earlier Neolithic groups than to the DNA of all other populations related to the Pontic steppe migration. Explicit comparisons of alternative demographic models via approximate Bayesian computation confirmed this pattern. These results are not in contrast to Late Neolithic gene flow from the Pontic steppes into Central Europe. However, they add nuance to this model, showing that the eastern affinities of the GAC in the archaeological record reflect cultural influences from other groups from the East, rather than the movement of people.